Incidencia de Dirofilaria immitis en perros de la parroquia urbana del cantón Chone provincia de Manabí - Bravo Arteaga, Anacelia Jeniret (2023)
The investigation was carried out in the urban parish in Chone, Manabí province; the goal was to evaluate the prevalence of Dirofilaria immitis in random dogs belonging to different sectors. The dog sample was obtained from the last Chone rabies vaccination campaign report (2020) by means of a finite population at 90% confidence, resulting in 70 samples, which were analyzed by means of the thick blood smear test; the risk factors were also evaluated through the use of surveys: genetic group, age, habitat, deworming and sex; the general prevalence obtained using the percentage method was 8.57% and all the positive cases (60%) came from the El Vergel neighborhood. Of the total number of positive animals, the highest percentage was found in mestizos 66.67%, aged 5 months to 72 months with 66.66%, who were indoors 50%, also in dogs whose last deworming was more than of three months 66.67%, with deworming of the active principle pyrantel plus praziquantel 83.08% and in relation to sex the prevalence had an equal distribution, in addition, the Pearson Chi-square χ2 test was used at 5% error through the statistical software InfoStat version 2020 to identify the relationship between risk factors and also with positive cases; in it it was evidenced that the factors under study are not directly related to the parasite, but there was statistical significance between the sets of genetic group - deworming (p=0.01) and between habitat and type of antiparasitic (p=0,04).